FAKTOR-FAKTOR YANG MEMPENGARUHI PERATAAN LABA PADA PERUSAHAAN NON KEUANGAN YANG TERDAPAT PADA BURSA EFEK INDONESIA PERIODE 2018-2020 - Stella Gabriela (Universitas Sains dan Teknologi Komputer, 2023)
The practice of income smoothing is a common phenomenon that occurs as a management effort to reduce reported profit fluctuations. This study aims to determine the effect of managerial ownership, institutional ownership, Net Profit Margin, Cash Holding, Bonus Plan, and dividend payout ratio on income smoothing practices. The sample of this research is non-financial companies that are listed on the Indonesia Stock Exchange in 2018-2020. Data obtained from www.idx.co.id. Logistic regression analysis model with SPSS. The conclusion in this study is that managerial ownership, institutional ownership, Net Profit Margin, Cash Holding, and dividend payout ratio have a significant positive effect on income smoothing. Meanwhile Bonus Plan did not have significant effect on income smoothing.